2021
DOI: 10.1007/s10565-021-09634-9
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of calpain reduces cell apoptosis by suppressing mitochondrial fission in acute viral myocarditis

Abstract: Cardiomyocyte apoptosis is critical for the development of viral myocarditis (VMC), which is one of the leading causes of cardiac sudden death in young adults. Our previous studies have demonstrated that elevated calpain activity is involved in the pathogenesis of VMC. This study aimed to further explore the underlying mechanisms. Neonatal rat cardiomyocytes (NRCMs) and transgenic mice overexpressing calpastatin were infected with coxsackievirus B3 (CVB3) to establish a VMC model. Apoptosis was detected with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Inhibiting mitochondrial permeability transition pore opening through cyclosporin A treatment reduced Abcc6-dependent cardiac necrosis and calcification following CVB3 infection in mice [ 35 ]. Furthermore, curtailing excessive mitochondrial fission with Dynamin-related protein 1 inhibitor rescued myocardial injury induced by CVB3 [ 44 ]. However, the precise molecular mechanisms underlying the association between mitochondria and myocarditis development need to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting mitochondrial permeability transition pore opening through cyclosporin A treatment reduced Abcc6-dependent cardiac necrosis and calcification following CVB3 infection in mice [ 35 ]. Furthermore, curtailing excessive mitochondrial fission with Dynamin-related protein 1 inhibitor rescued myocardial injury induced by CVB3 [ 44 ]. However, the precise molecular mechanisms underlying the association between mitochondria and myocarditis development need to be investigated further.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, under pathological stress, mitochondrial dynamin-related protein-1 (Drp1) as a key mitochondrial regulatory protein predominantly interacts with fission 1 (Fis1), causing an exaggerated fission process, as evidenced by excessive mitochondrial fragmentation, production of reactive oxygen species (ROS) and loss of mitochondrial membrane potential [ 10 ]. Therefore, marked pathological fragmentation of mitochondria is produced, and mitochondrial function is significantly disrupted by decreasing adenosine triphosphate (ATP) and mitochondria membrane potential [ 11 ]. Finally, damaged astrocytic mitochondria are further released, enter adjacent neurons and induce fusion with neuronal mitochondria, inducing neuronal mitochondrial dysfunction, amplifying neuronal damage and worsening neurological outcomes [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Calpain-1, activated by Ca 2+ influx, is a key downstream target of TRPC6 ( Zhang et al, 2014 ; Verheijden et al, 2018 ). Previous studies have shown that the activation of calpain induces mitochondrial fission by mediating Drp1 phosphorylation, resulting in myocardial apoptosis ( Shi et al, 2021 ; Zhang et al, 2021 ). Studies have identified that inhibition of either calpain or calcineurin leads to downregulated Drp1 and Fis1 levels, and upregulated Opa1 levels and MMP during exposure to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Calpain-1, one of the nonlysosomal cysteine proteases consisting of an 80 kDa isoform-specific catalytic domain, has been widely demonstrated to be activated by TRPC6-dependent Ca 2+ influx in podocytes ( Verheijden et al, 2018 ). The effect of calpain-1 on mitochondrial fission has been reported in cardiac diseases ( Shi et al, 2021 ), whereas it is unclear in podocytes.…”
Section: Introductionmentioning
confidence: 99%